Experimental research of hydrodynamic characteristics during boiling of refrigerants in minichannels using true parameters of phases - A. A. Malyshev; A. V. Zaitsev; K. F. Kuadio; K. V. Kisser (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
This paper is devoted to the development of an integrated method for calculating heat hydrodynamic characteristics of two-phase flows taking into account the specificity of the flow in minichannels. The proposed approach is based on the methodology for calculating the true volumetric vapor quality and the prediction of two-phase flow regimes. The paper presents experimental data on true volumetric vapor quality and a modified map of flow regimes